2020
DOI: 10.1177/8755293020952461
|View full text |Cite
|
Sign up to set email alerts
|

Constant-ductility energy factors of SDOF systems subjected to mainshock–aftershock sequences

Abstract: This article focuses on the energy factor of single-degree-of-freedom (SDOF) systems subjected to mainshock–aftershock (MSAS) sequences, of which 163 and 143 are collected from crustal and subduction regions, respectively. The recorded MSAS sequences are divided into four groups based on the relative intensity that is defined as the ratio of the peak ground acceleration ( PGA) of an aftershock to the PGA of the corresponding mainshock. Constant-ductility inelastic spectra are calculated to assess the energy fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Rosso et al [10] analyzed the corrosion effects on the capacity and ductility of concrete half-joint bridges. Ji et al [11] studied the effect of the ductility demand coefficient on the constant-ductility strength demand spectrum, and they found that, with an increase or decrease in the ductility demand coefficient, the strength demand coefficient and the seismic resistance coefficient showed a specific variation law. In addition, the effects of k 2 , ζ, the hysteretic model, and pinching on the constant-strength ductility demand spectrum were also studied [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rosso et al [10] analyzed the corrosion effects on the capacity and ductility of concrete half-joint bridges. Ji et al [11] studied the effect of the ductility demand coefficient on the constant-ductility strength demand spectrum, and they found that, with an increase or decrease in the ductility demand coefficient, the strength demand coefficient and the seismic resistance coefficient showed a specific variation law. In addition, the effects of k 2 , ζ, the hysteretic model, and pinching on the constant-strength ductility demand spectrum were also studied [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%